2005
DOI: 10.1161/01.hyp.0000188052.69549.e4
|View full text |Cite
|
Sign up to set email alerts
|

Neurocirculatory Abnormalities in Parkinson Disease With Orthostatic Hypotension

Abstract: Abstract-Patients with Parkinson disease often have orthostatic hypotension. Neurocirculatory abnormalities underlying orthostatic hypotension might reflect levodopa treatment. Sixty-six Parkinson disease patients (36 with orthostatic hypotension, 15 off and 21 on levodopa; 30 without orthostatic hypotension) had tests of reflexive cardiovagal gain (decrease in interbeat interval per unit decrease in systolic pressure during the Valsalva maneuver; orthostatic increase in heart rate per unit decrease in pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 59 publications
4
86
0
4
Order By: Relevance
“…We did not find a significant difference in basal norepinephrine levels between the groups, in contrast to other studies (14,15,39,40), although norepinephrine in our study tended to be lower in PD ϩ OH. The lack of a norepinephrine difference could be due to larger standard deviations of norepinephrine levels in our PD patients who are treated with levodopa (16). Although norepinephrine is a potent vasoconstrictor, vascular tone is regulated by a combination of several vasoconstrictors and dilators.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We did not find a significant difference in basal norepinephrine levels between the groups, in contrast to other studies (14,15,39,40), although norepinephrine in our study tended to be lower in PD ϩ OH. The lack of a norepinephrine difference could be due to larger standard deviations of norepinephrine levels in our PD patients who are treated with levodopa (16). Although norepinephrine is a potent vasoconstrictor, vascular tone is regulated by a combination of several vasoconstrictors and dilators.…”
Section: Discussionmentioning
confidence: 91%
“…PD patients have a reduced baroreflex cardiovagal function, denervation of the heart, low norepinephrine levels, and no increment in norepinephrine levels during orthostatic challenges (14,39). However, baroreflex failure and cardiac sympathetic denervation contribute to but cannot fully explain OH in PD (14,16).…”
mentioning
confidence: 99%
“…Some studies have shown BRS to be similarly low in PD and MSA. [5][6][7] while others have shown it to be significantly smaller in MSA. 8 These previous studies are subject to a few important caveats.…”
Section: Introductionmentioning
confidence: 94%
“…It is well documented that MSA-C patients (MSA of the cerebellar type) and MSA-P patients show differences in both the severity and onset of OH 9 and it is noteworthy that several studies combined these patients in their analyses. 7,8 It has also been demonstrated that BRS is lower in Parkinson's disease patients with orthostatic hypotension (PDOH) than in those without OH 5,10 and that a lower BRS is correlated with a higher score on the Hoehn and Yahr scale of severity. 8 BRS has also been shown to differ between males and females.…”
Section: Jcnmentioning
confidence: 99%
See 1 more Smart Citation